Kolaborasi Kerja Bakti Masyarakat dalam Mencegah Terjadinya Bencana Banjir di Wilayah Sidoarjo - Muhammad Yusron Maulana El-Yunusi; Mukhamad Bakhrul Ulum; Rahayu Mardikaningsih; Mirza Elmy Safira; Didit Darmawan (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Collaborative activities explain the strategic meaning of collaborative community service by the Sidoarjo Regency Government together with all levels of the local community as an effort to prevent flooding, findings in the field show that urban flooding is not solely caused by high rainfall, but is triggered by low individual environmental awareness. The purpose of this collaborative activity focuses on maintaining the cleanliness of the River Basin (DAS) which functions as an area and the main factor in disasters and the important role of the government in facilitating this collaboration to maximize potential. This article uses a Participatory Action Research (PAR) approach. This activity attracted broad participation from various parties, including the district government, city government, the Indonesian National Armed Forces (TNI), academics, and community elements. The synergy between the use of heavy equipment and the mobilization of community labor ensured that the cleaning of garbage and water hyacinth was carried out comprehensively, while strengthening social cohesion between the elements involved. The results of this activity achieved dual success: physically (significant river cleanup) and socially, fostering a spirit of cooperation and collective critical awareness among the community regarding the importance of maintaining a clean environment. The conclusion was that this activity proved effective not only as a flood prevention measure but also as a means of strengthening social bonds. It is recommended that similar activities be held periodically to strengthen the collective commitment and solidarity of the Sidoarjo community.